PARENTHOOD READINESS: MODUL BIMBINGAN KELOMPOK BAGI REMAJA DENGAN KEHAMILAN TIDAK DIINGINKAN - Dara Denanti, Salsabila; Windrawanto, Yustinus; Maria Agustin, Adhi Krisna (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Unwanted pregnancy in adolescents can pose various challenges, including readiness to play the role of parents (parenthood readiness). This study aims to determine the effectiveness of the group guidance module in overcoming and handling parenthood readiness in adolescents with unwanted pregnancies. The method used is research and development, with a 4D model approach that includes the stages of definition, design, development, and dissemination. This module is designed to improve adolescent readiness in emotional, social, financial, and parenthood aspects. The results of validation from 3 experts and trials indicate that this module is suitable for use as a guidance medium for adolescents with unwanted pregnancies.